2022
DOI: 10.1287/mnsc.2021.4090
|View full text |Cite
|
Sign up to set email alerts
|

The Wisdom of Model Crowds

Abstract: A wide body of empirical research has revealed the descriptive shortcomings of expected value and expected utility models of risky decision making. In response, numerous models have been advanced to predict and explain people’s choices between gambles. Although some of these models have had a great impact in the behavioral, social, and management sciences, there is little consensus about which model offers the best account of choice behavior. In this paper, we conduct a large-scale comparison of 58 prominent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 113 publications
0
18
0
Order By: Relevance
“…(Note, however, that that this result is not trivial, as the penalty incurred by Models 2-4 for including additional parameters could have caused them to lose the comparison.) Indeed, previous studies have shown (using large-scale datasets) that EV alone is not the best model for choice (He et al, 2022;Peterson et al, 2021). To increase the ability of the integrate-then-compare model (Model 1) to explain the data, we considered a variant where in the place of EV for each option we calculated subjective utility as under Prospect Theory (Tversky & Kahneman, 1992).…”
Section: Model Comparisonmentioning
confidence: 99%
“…(Note, however, that that this result is not trivial, as the penalty incurred by Models 2-4 for including additional parameters could have caused them to lose the comparison.) Indeed, previous studies have shown (using large-scale datasets) that EV alone is not the best model for choice (He et al, 2022;Peterson et al, 2021). To increase the ability of the integrate-then-compare model (Model 1) to explain the data, we considered a variant where in the place of EV for each option we calculated subjective utility as under Prospect Theory (Tversky & Kahneman, 1992).…”
Section: Model Comparisonmentioning
confidence: 99%
“…An alternative view involves the notion of models as collaborative crowds rather than as fierce competitors. He et al (2021) suggested that when there is no unequivocal best-performing model for individual findings, the aggregation of models can flexibly account for larger shares of data using the "wisdom of crowds." Accordingly, this exploits the unique complementarities of different models, bringing the research field closer to reaching its full potential.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…However, this model is limited in terms of scalablity and adaptability. For example, it cannot be easily trained and provide predictions for new data (Peterson et al, 2021;He et al, 2022).…”
Section: Introductionmentioning
confidence: 99%